Premeditated Murder in the Modern Era Comparative Study of Perspectives on Islamic Law and the Criminal Code - Tina Oktatianti; Mahmoud Saleh Mubarak Bin Humaid; Rozi Irfan Rosyadi; Ahmadi Abdul Adzim; Muthoifin (Solo International Collaboration and Publication of Social Sciences and Humanities, 2023)
This study tries to 1) identify the elements that lead murderers to plan their crimes, and 2) understand those elements. The judge's factors to consider when determining murder cases with intent to kill, 3). Comparing the Criminal Code with Islamic law's definition of premeditated murder. To gather data for this study, a library research technique known as a normative juridical approach to literature evaluation was used. The Criminal Code, followed by the Koran, Hadith, and translations into Indonesian, as well as relevant scholarly works, books, and articles, served as the source for legal information. The study's findings led to the conclusion that Indonesian law's Criminal Code Articles 338–350 govern the crime of murder. In the Criminal Code, premeditated murder is defined as a purposeful killing, whereas in Islamic criminal law, the victim's life is the first thing that is intended to be taken. According to Article 340 of the Criminal Code, the perpetrator of a premeditated murder may be sentenced to life in prison by a jury of judges. Whereas in Islamic criminal law, as mentioned in QS. Al-Maidah verse 45 and Hadith, the perpetrator's acts might result in a death sentence (Qishash) for committing purposeful murder.